2006
DOI: 10.1200/jco.2005.03.4074
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Resistance to Interferon-Induced Apoptosis of Renal Carcinoma and Melanoma Cells by DNA Demethylation

Abstract: Epigenetic editing of gene expression by aberrant methylation of DNA may help tumor cells escape attack from the innate and acquired immune systems. Resistance to antiproliferative effects and apoptosis induction by interferons (IFNs) was postulated to result from silencing of IFN response genes by promoter hypermethylation. Treatment of human ACHN renal cell carcinoma (RCC) and A375 melanoma cells with the DNA demethylating nucleoside analog 5-AZA-2'-deoxycytidine (5-AZA-dC) synergistically augmented antiprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 45 publications
3
105
0
Order By: Relevance
“…17,[31][32][33][34] Epigenetic silencing of the XAF1 gene by aberrant promoter methylation appears to correlate with the malignant progression of human gastric tumors. 18,33 In our study, we demonstrate that overexpression of XAF1 suppressed anchorage-dependent and -independent growth.…”
Section: Discussionmentioning
confidence: 99%
“…17,[31][32][33][34] Epigenetic silencing of the XAF1 gene by aberrant promoter methylation appears to correlate with the malignant progression of human gastric tumors. 18,33 In our study, we demonstrate that overexpression of XAF1 suppressed anchorage-dependent and -independent growth.…”
Section: Discussionmentioning
confidence: 99%
“…XAF1 interacts with an inhibitor of apoptosis (XIAP) that may function as a competitive inhibitor of caspases to play a critical role in TRAIL-induced apoptosis (Deveraux et al, 1997;Liston et al, 2001;Leaman et al, 2002;Chawla-Sarkar et al, 2004). XAF1 has been silenced by DNA methylation in gastric cancer and is frequently reduced in expression in melanoma (Byun et al, 2003;Ng et al, 2004;Reu et al, 2006a). However, in SK-MEL-3 and SK-MEL-28 cells, 5-AZAdC had a marginal effect on XAF1 mRNA expression (Table 1).…”
Section: Role Of Trail In Sensitization To Ifns By 5-azadcmentioning
confidence: 99%
“…Silencing of genes involved in signaling downstream of interferon, such as interferon regulatory factor 8 and XIAPassociated factor 1 trigger resistance of tumor cells to interferon therapy (Reu et al, 2006;Yang et al, 2007). However, injection of decitabine in nude mice carrying melanoma xenografts led to resensitization to interferon treatment (Reu et al, 2006). A phase I clinical trial of decitabine together with interleukin-2 in melanoma patients further showed an objective response in 31% of the patients (Gollob et al, 2006).…”
Section: Epigenetic Cancer Therapymentioning
confidence: 99%
“…In melanoma, for instance, one of the standard treatments is interferon, which induces tumor apoptosis, differentiation and increases the anti-tumor immune response. Silencing of genes involved in signaling downstream of interferon, such as interferon regulatory factor 8 and XIAPassociated factor 1 trigger resistance of tumor cells to interferon therapy (Reu et al, 2006;Yang et al, 2007). However, injection of decitabine in nude mice carrying melanoma xenografts led to resensitization to interferon treatment (Reu et al, 2006).…”
Section: Epigenetic Cancer Therapymentioning
confidence: 99%